Mx1‐Cre mediated Rgs12 conditional knockout mice exhibit increased bone mass phenotype. Issue 3 (25th February 2013) - Yang, Shuying; Li, Yi‐Ping; Liu, Tongjun; He, Xiaoning; Yuan, Xue; Li, Chunyi; Cao, Jay; Kim, Yunjung
Summary Regulators of G‐protein Signaling (Rgs) proteins are the members of a multigene family of GTPase‐accelerating proteins (GAP) for the Galpha subunit of heterotrimeric G‐proteins. Rgs proteins play critical roles in the regulation of G protein couple receptor (GPCR) signaling in normal physiology and human diseases such as cancer, heart diseases, and inflammation. Rgs12 is the largest protein of the Rgs protein family. Some in vitro studies have demonstrated that Rgs12 plays a critical role in regulating cell differentiation and migration; however its function and mechanism in vivo is largely unknown. Here, we generated a floxed Rgs12 allele (Rgs12flox/flox) in which the exon 2, containing both PDZ and PTB_PID domains of Rgs12, was flanked with two loxp sites. By using the inducible Mx1‐cre and Poly I:C system to specifically delete Rgs12 at postnatal 10 days in interferon‐responsive cells including monocyte and macrophage cells, we found that Rgs12 mutant mice had growth retardation with the phenotype of increased bone mass. We further found that deletion of Rgs12 reduced osteoclast numbers and had no significant effect on osteoblast formation. Thus, Rgs12flox/flox conditional mice provide a valuable tool for in vivo analysis of Rgs12 function and mechanism through time‐ and cell‐specific deletion of Rgs12. genesis 51:201–209, 2013. © 2013 Wiley Periodicals, Inc.